Comparative Analysis of Cloves Drying Machines - Mansyur, Mansyur; Ali, Andi Muhammad Taufik; Muflihat, Syakia (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This research addresses the critical need to systematically benchmark the efficiency of modern drying machine to upgrade the prevailing traditional method for drying cloves. The main objective of this investigation was to analyze comparative efficiency between electric and biomass dryig machine and provide recommendations for the most optimal type of drying machine based on energy consumption, drying time and final moisture content. This study using comparatibe experimental design with controlled cloves samples to collect data and applied one-way ANOVA test for the statictical analysis of significant differences betweeen the machines. The results confirmed that the electric drying machine achieves greates overall efficiency and optimality, providing faster processing times without diminishing the basic quality or final moisture content of the cloves.